Ação antiagregante e moduladora da função vascular da β-glucana extraída de Saccharomyces cerevisae e da forma carboximetilada derivada - Bezerra, Lorena Soares (2016)
The β-D-glucans are polysaccharides constituting the cell wall of yeasts such as Saccharomyces cerevisiae. Evidence shows polymers have several beneficial effects, mainly related to immunomodulation. However, their action on platelet and endothelial function is understudied. This study aimed to evaluate the effect of (1-3) (1-6) β-D-glucan extracted from S. cerevisiae and derivative carboxymethylated (CM-G) on vascular and platelet function in rats. The animals were treated orally with CM-G and BG-Sc at a dose of 20 mg/kg daily for eight days and the controls received saline as placebo. At end, were collected blood and thoracic aortic artery to study platelet activation and aggregation by light transmission, flow cytometry, vascular reactivity and cytokine assay. In vitro studies of platelet activation and aggregation induced by adenosine diphosphate (ADP) and collagen were conducted with CM-G at different concentrations (100 and 300 μg/mL). Significant reduction in IL-8 levels (4,18 ± 0,72 pg/mL) in the group treated with CM-G was also found when compared to control (22,7 ± 6,9 pg/mL) and the BG-Sc group (16,4 ± 2,4 pg/mL). The reactivity studies shows BG-Sc and CM-G had no influence on vascular response to phenylephrine (PHE) compared to the control. In the group treated with BG-SC, the response to vasorelaxantes agents such as acetylcholine (ACH; Emax = 90,2 ± 14,1%; pD2 = 6,36 ± 0,30 M) and sodium nitroprusside (SNP; Emax = 92,3 ± 2,4%; pD2 = 10,21 ± 0,10M) were impaired compared to controls (ACH: Emax = 100 ± 7,5%; pD2 = 8,17 ± 0,25 M; SNP: Emax = 100 ± 9,5%; pD2 = 11,18 ± 0,27 M). However, treatment with CM-G (max = 93,1 ± 2,7%; pD2 = 11,71 ± 0,07 M) increased the potency of NPS when compared with the control (Emax = 100 ± 9.5%; pD2 = 11.18 ± 0.27). In vitro studies of platelet aggregation by light transmission reveals CM-G inhibited the aggregation stimulated by ADP in doses of 100 and 300 mg/ml, reaching 25,7 ± 2,7% and 14,8 ± 3,2% of aggregation, respectively. When aggregation was induced by collagen, only the dose 300 mg/ml had inhibitory activity (33 ± 6,2%). The antiplatelet effect was similar to acetylsalicylic acid when the aggregation was generate by ADP. Aggregation inhibition was also demonstrated by flow cytometry, however was observed that CM-G had no effect on platelet activation. In treated animals, there was inhibition of platelet aggregation induced by ADP (45% ± 3,9 and 45 ± 6%, respectively). However, when induced by collagen, antiplatelet effect was observed only in animals receiving the BG-Sc (22,6 ± 7,7%). The treatment and in vitro aggregation assays suggest that CM-G appears to be more selective for ADP. The findings indicate the CM-G and BG-Sc feature antiplatelet effect and modulating vascular function. Thus, the use of these polysaccharides may be a possible tool for the prevention of cardiovascular diseases